AN LC-MS/MS METHOD DEVELOPMENT AND VALIDATION FOR THE QUANTIFICATION OF ANTIVIRAL DRUGS IN PLASMA SAMPLES - G., DIVYA; STV, RAGHAVAMMA (International Journal of Applied Pharmaceutics, 2026)
Objective: A reliable and specific LC-MS/MS method was developed and validated for the simultaneous quantification of cabotegravir (CBTG) and rilpivirine (RLPV) in plasma samples. Methods: Chromatographic separation was achieved on a Hypersil BDS C18 (50 × 4.6 mm, 5 µm) column maintained at 35 °C. The mobile phase consisted of 0.1% HCOOH, acetonitrile, and methanol in the ratio 10:80:10 (v/v/v). The injection volume was 10 µl**, and the autosampler temperature was maintained at 10 °C. The retention times for RLPV, internal standard, and CBTG were 2.00, 3.20, and 5.15 min, respectively. Results: Accuracy ranged from 96.32% to 98.19% for CBTG and 95.57% to 97.00% for RLPV. The intra-and inter-day precision values were 0.39%–3.82% RSD for CBTG and 1.56%–4.55% RSD for RLPV mean recovery values at three QC levels were 96.14%–97.70% for CBTG and 96.06%–97.75% for RLPV. All stability assessments were within acceptance criteria. Conclusion: The method is robust for the quantitative determination of CBTG and RLPV in biological samples and is suitable for application in forensic, quality-control, bioavailability, and bioequivalence studies.